2019
DOI: 10.1177/0954406219830732
|View full text |Cite
|
Sign up to set email alerts
|

A review on research progress of machining technologies of carbon fiber-reinforced polymer and aramid fiber-reinforced polymer

Abstract: Since the application of fiber-reinforced polymer continues to expand, the demands of product quality for secondary cutting process are becoming increasingly higher to ensure the accurate coordination, connection, and assembly. There are some defects such as tearing, burr, delamination, and thermal damage after secondary cutting process, which limit the further applications of the materials. It is urgent to carry out comprehensive research on the secondary processing technology. In this paper, the fiber-reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 44 publications
(40 reference statements)
1
15
0
Order By: Relevance
“…It dropped down slightly as the increasing of cutting speed until 10,000 r/min as found in previous studies. 22,24,30,47 It can be explained by the reduction in tool wear the decreasing of cavity volume as verified by Fuji et al 48 Then its variation was changed to slight elevation with cutting speed which is verified by some of studies 23,36,48 as well, and it can be explained by the warming and creating of heat affected zone in machined surface with high cutting speed that leads to the degradation of matrix and melting of fibers and affecting the surface roughness.…”
Section: Responses Surface Methodology Analysis (Rsm)mentioning
confidence: 82%
See 1 more Smart Citation
“…It dropped down slightly as the increasing of cutting speed until 10,000 r/min as found in previous studies. 22,24,30,47 It can be explained by the reduction in tool wear the decreasing of cavity volume as verified by Fuji et al 48 Then its variation was changed to slight elevation with cutting speed which is verified by some of studies 23,36,48 as well, and it can be explained by the warming and creating of heat affected zone in machined surface with high cutting speed that leads to the degradation of matrix and melting of fibers and affecting the surface roughness.…”
Section: Responses Surface Methodology Analysis (Rsm)mentioning
confidence: 82%
“…So the optimum surface roughness quality was obtained with the cutting tools with a low number of flutes and acute helix angle. 27,[29][30][31] Cherif et al 32 confirmed that the profile obtained for surface roughness measurement along the hole surface of a composite laminate depends significantly on the angular position of measurement. In order to characterize the roughness of the drilled hole in a composite laminate, it is essential to measure several profiles over a minimum angular extent of 90 .…”
Section: Introductionmentioning
confidence: 95%
“…The authors summarized that the quality of the hole can be enhanced by low feeds and high spindle speeds. Shi et al 10 reviewed the compound machining processes (ultrasonic-assisted mechanical machining and cutting-grinding compound machining) during drilling of CFRP and aramid fiber-reinforced polymer (AFRP). The authors found that burr (delaminated fibers) and tear defects are effectively controlled during the process.…”
Section: Introductionmentioning
confidence: 99%
“…Modern manufacturing demands strategies for machining fibrous composites because of their wide range of applications due to some peculiarities such as high strength at low weight, high creep, good wear and corrosion resistance, low density, low thermal expansion coefficient, and high dimensional stability. [1][2][3][4][5][6][7][8][9] Nowadays, the carbon fiber reinforced polymer (CFRP) is mostly adopted in aerospace industries for fabricating critical parts of modern aircraft, [1][2][3] fabrication of sporting items, 2 defence applications, 2,4 and chemical industries 4,5 because of its significant characteristics. Requirements of a smooth hole with low delamination, burr formation, taper, better circularity, and high processing speed set challenges for conventional machining processes.…”
Section: Introductionmentioning
confidence: 99%